Basic ISO standards related to the quality and safety/security in health care institutions - Pendić Zoran R.; Pendić-Polak Sanja Z.; Milijić Ana M.; Jakovljević Bojana B.; Marković Željko M.; Reljić-Ćurić Vesna M.; Ivošević Sanja J. (Tehnika, 2022)
Health systems are under significant pressure in many countries. Every day, with the introduction of new methods/techniques, expensive equipment of high technological value, the latest very expensive drugs... the price of health care is growing much faster than the growth of the national product and the most developed countries, despite the fact that in many countries the percentage of health expenditures in the national product is growing. Funding constraints in health systems are evident even in wealthy countries. The cost of health care is significantly influenced by: the increase in the number of the population, changes in the age structure of the population, constant demands for increasing the level of quality of health services, as well as an increase in the demand for new services. The application of international management standards in healthcare institutions and in state institutions in charge of healthcare can significantly alleviate evident problems in healthcare.